2015
DOI: 10.1007/s00415-015-7668-9
|View full text |Cite
|
Sign up to set email alerts
|

Criteria improving multiple sclerosis diagnosis at the first MRI

Abstract: The introduction of the McDonald criteria has enabled earlier diagnosis of multiple sclerosis (MS). However, even with the 2010 revised criteria, nearly 50% of patients remain classified as "possible MS" following the first MRI. The present study aimed to demonstrate that time to MS diagnosis could be shorter than 2010 revised criteria, and established after a single early MRI in most patients with the association of the symptomatic lesion and at least one suggestive asymptomatic lesion. We also evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…The HR of MS was higher for patients with a symptomatic lesion (HR=7.2) than for those with a single asymptomatic lesion (HR=5.7), or with no lesions (HR=1), in the same regions. Another retrospective study in 146 CIS patients who fulfilled the 2010 McDonald criteria 10 found that the presence of a symptomatic lesion identifies with a high sensitivity those patients with MS. 13 In a recent study of 30 CIS patients who were studied for a mean of 7.3 years after onset, the sensitivity/specificity/accuracy of the DIS criteria was 73/73/73% for the 2010 McDonald criteria, 80/73/77% when asymptomatic lesions in the symptomatic region were included, and 87/73/80% when any lesion in the symptomatic region was included. 14 These results suggest that including lesions in the symptomatic region in DIS may increase the sensitivity of MRI criteria for diagnosing MS without compromising specificity.…”
Section: Methodsmentioning
confidence: 97%
“…The HR of MS was higher for patients with a symptomatic lesion (HR=7.2) than for those with a single asymptomatic lesion (HR=5.7), or with no lesions (HR=1), in the same regions. Another retrospective study in 146 CIS patients who fulfilled the 2010 McDonald criteria 10 found that the presence of a symptomatic lesion identifies with a high sensitivity those patients with MS. 13 In a recent study of 30 CIS patients who were studied for a mean of 7.3 years after onset, the sensitivity/specificity/accuracy of the DIS criteria was 73/73/73% for the 2010 McDonald criteria, 80/73/77% when asymptomatic lesions in the symptomatic region were included, and 87/73/80% when any lesion in the symptomatic region was included. 14 These results suggest that including lesions in the symptomatic region in DIS may increase the sensitivity of MRI criteria for diagnosing MS without compromising specificity.…”
Section: Methodsmentioning
confidence: 97%
“…Especially the interaction between leukocortical lesions and global network metrics such as modularity and density were associated with SDMT outcomes. Due to their location in the lower part of the cortex and superficial white matter, leukocortical lesions affect short association fibers connecting two cortical gyri below the cortex (i.e., U-fibers) ( Caucheteux et al, 2015 ), whose disruption has been previously associated with memory and executive function impairment ( Miki et al, 1998 ; Rovaris et al, 2000 ). Our results confirm previous findings reporting an association between juxtacortical lesions and cognitive deficits in pwMS ( Lazeron et al, 2000 ; Louapre et al, 2016 ; Shaaban et al, 2021 ), and further elucidate the mechanisms underlying this association.…”
Section: Discussionmentioning
confidence: 99%
“… 8 In fact, some studies reported that the presence of a symptomatic lesion identified patients with MS with a high sensitivity and accuracy and without compromising specificity. 9 10 11 …”
Section: Discussionmentioning
confidence: 99%